A survey on edge computing offloading - Youkang ZHU; Guangxue YUE; Xiaohui YANG; Jiansheng LIU (Dianxin kexue)
Edge computing integrate the computing,storage and other resources on the edge of the network into a unified user service platform.According to the principle of nearest service,the network edge node task request is timely and correspondingly processed.Computational migration is a key issue in edge computing due to limited edge node capabilities,resources,bandwidth,and energy.The causes,evolution and development trends of mobile edge computing were reviewed from the distributed computing,pervasive computing,cloud computing to edge computing as the main line.The characteristics of computing migration at each stage were compared and analyzed,and the classical models were reviewed.The latest research progress and application fields of edge computing were focused on,mobile edge computing models based on energy optimization management were researched and compared.Finally,a time division multiple access based multi-user edge mobile terminal computing migration strategy system for LTE applications was proposed.